2021
DOI: 10.3389/fpls.2021.662793
|View full text |Cite
|
Sign up to set email alerts
|

Illuminating the COP1/SPA Ubiquitin Ligase: Fresh Insights Into Its Structure and Functions During Plant Photomorphogenesis

Abstract: CONSTITUTIVE PHOTOMORPHOGENIC 1 functions as an E3 ubiquitin ligase in plants and animals. Discovered originally in Arabidopsis thaliana, COP1 acts in a complex with SPA proteins as a central repressor of light-mediated responses in plants. By ubiquitinating and promoting the degradation of several substrates, COP1/SPA regulates many aspects of plant growth, development and metabolism. In contrast to plants, human COP1 acts as a crucial regulator of tumorigenesis. In this review, we discuss the recent importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 227 publications
(309 reference statements)
1
55
0
Order By: Relevance
“…The ER stress-sensitive phenotype of cop1-4 was fully rescued by complementation with constructs expressing COP1 and COP1 L105A but not by those expressing COP1 L170A and COP1 MUT ( Figure 3 , Figures S3 and S4 ). These results are consistent with those of previous studies, which showed that the nuclear localization of COP1 is important for regulation of its target proteins, which is needed to suppress photomorphogenesis [ 25 , 32 , 40 , 41 ]. Despite the nuclear localization of the COP1 L170A , complementation of the cop1-4 mutant with COP1 L170A failed to rescue its ER stress-sensitive phenotype and to normalize its photomorphogenic response ( Figure 3 , Figures S3 and S4 ).…”
Section: Discussionsupporting
confidence: 93%
“…The ER stress-sensitive phenotype of cop1-4 was fully rescued by complementation with constructs expressing COP1 and COP1 L105A but not by those expressing COP1 L170A and COP1 MUT ( Figure 3 , Figures S3 and S4 ). These results are consistent with those of previous studies, which showed that the nuclear localization of COP1 is important for regulation of its target proteins, which is needed to suppress photomorphogenesis [ 25 , 32 , 40 , 41 ]. Despite the nuclear localization of the COP1 L170A , complementation of the cop1-4 mutant with COP1 L170A failed to rescue its ER stress-sensitive phenotype and to normalize its photomorphogenic response ( Figure 3 , Figures S3 and S4 ).…”
Section: Discussionsupporting
confidence: 93%
“…The CCT domains of CRY1 and CRY2 interact with COP1 ( Wang et al, 2001 ; Yang et al, 2001 ; Ponnu et al, 2019 ), an E3 ubiquitin ligase that inhibits light signaling by polyubiquitinating multiple transcription factors acting in the various light responses. COP1 is mainly active in darkness, thereby preventing an accumulation of these substrate transcription factors which leads to a suppression of light responses in darkness ( Huang et al, 2014 ; Hoecker, 2017 ; Ponnu and Hoecker, 2021 ). Epistatic analyses of cop1 and cry1 mutants suggested early on that CRYs initiate light signaling in blue light by inhibiting the activity of COP1 ( Ang and Deng, 1994 ; Figures 1 , 2 ).…”
Section: Signal Transduction Through Cryptochrome-interacting Proteinsmentioning
confidence: 99%
“…After phytochrome or cryptochrome activation by light, these photoreceptors inhibit the COP1/SPA activity, causing stabilization of the targeted transcription factors and subsequent light response. More than two dozens of transcription factors have so far been identified as COP1/SPA targets, including HYPOCOTYL5 (HY5), CONSTANS and PRODUCTION OF ANTHOCYANIN PIGMENT1 (PAP1)/PAP2, and many of them share a conserved COP1‐binding motif consisting of a valine–proline (VP) sequence (Ponnu & Hoecker, 2021).…”
Section: Introductionmentioning
confidence: 99%